Recent Progress in Advanced Characterization Methods for Silicon‐Based Lithium‐Ion Batteries. Issue 10 (14th May 2019) - Wu, Jingkun; Ma, Fei; Liu, Xiaorui; Fan, Xiayue; Shen, Long; Wu, Zhihong; Ding, Xiaoyang; Han, Xiaopeng; Deng, Yida; Hu, Wenbin; Zhong, Cheng
Abstract: With the remarkably large theoretical specific capacity of silicon (Si), Si‐based rechargeable lithium‐ion batteries (LIBs) have attracted great interest, as they are expected to meet the growing demand for large‐scale energy storage devices, electric vehicles, and portable electronic devices with high energy density. However, the Si‐based LIB faces great challenges due to the cyclic volume changes induced by Si, which lead to considerable capacity fading. To facilitate the use of high‐performance LIBs enabled by Si‐based anodes, understanding the fading mechanism is necessary. In this regard, various advanced characterization methods have been developed to reveal the fading mechanism and to develop a modification strategy associated with compositional and structural evolution. In this review, the general understanding of the fading mechanism and the technical specifications of Si‐based LIBs are discussed. The recent progress in advanced characterization methods for Si‐based LIBs is summarized with respect to the achievements in compositional and structural interpretation. Several possible future research directions for Si‐based LIBs and the expected development trends in relevant characterization methods are also discussed. Abstract : The recent advances and challenges in characterization methods for lithium‐ion batteries (LIB) based on silicon (Si)‐based anodes are reviewed. With the insights provided by development of characterization methods, materials in Si‐based LIBs with improved design are expected to facilitate the future applications.